COMPETITIVE ADVANTAGE AS A MEDIATOR ON THE INFLUENCE OF STRATEGIC LEADERSHIP, DYNAMIC CAPABILITIES, AND KNOWLEDGE MANAGEMENT ON ORGANIZATIONAL PERFORMANCE IN PT ELNUSA TBK - Satya Graha Gintings, I Ketut R Sudiadhita, Dewi Susita (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research proposal aims to examine and analyze 1) the influence of strategic leadership on competitive advantage, 2) the effect of dynamic capabilities on competitive advantage, 3) the influence of knowledge management on competitive advantage, 4) the effect of competitive advantage on organizational performance, 5) the effect of strategic leadership on organizational performance, 6) the influence of dynamic capabilities on organizational performance, 7) the influence of knowledge management on organizational performance, 8) the influence of strategic leadership on organizational performance through competitive advantage, 9) the influence of dynamic capabilities on organizational performance through competitive advantage, 10) the influence of knowledge management on organizational performance through competitive advantage. The research was conducted at PT Elnusa Tbk with a total sample size of 157 respondents. The sampling technique used purposive sampling and data analysis techniques used descriptive analysis and structural equation modeling. The research results predict 1) there is an effect of strategic leadership on competitive advantage, 2) there is an effect of dynamic capabilities on competitive advantage, 3) there is an effect of knowledge management on competitive advantage, 4) there is an effect of competitive advantage on organizational performance, 5) there is an effect of strategic leadership on organizational performance, 6) there is an effect of dynamic capabilities on organizational performance, 7) there is an influence of knowledge management on organizational performance, 8) there is an influence of strategic leadership on organizational performance through competitive advantage, 9) there is an effect of dynamic capabilities on organizational performance through competitive advantage, 10 ) there is the influence of knowledge management on organizational performance through competitive advantage.